Novel pathogenic variant in LMNA gene identified in a six-generation family causing atrial cardiomyopathy and associated right atrial conduction arrhythmias - Ning, Shifeng; Han, Min; Qiu, Rujie; Hong, Xiaoming; Xia, Zhao; Liu, Li; Liu, Chengwei (Frontiers in Cardiovascular Medicine, 2023)
Objective To characterize the cardiac phenotype associated with the novel pathogenic variant (c.1526del) of LMNA gene, which we identified in a large, six-generation family.A family tree was constructed. The clinical data of living and deceased family members were collected. DNA samples from 7 family members were analyzed for LMNA mutations using whole-exome high-throughput sequencing technology. The clinical presentation of pathogenic variant carriers was evaluated. In this six-generation family (n = 67), one member experienced sudden death at the age of 40-years-old. Three pathogenic variant carriers were identified to possess a novel heterozygous deletion mutation in LMNA gene (HGVS: NM_170707.4, c.1526del) located at exon 9 of LMNA chr1:156137145, which creates a premature translational stop signal (p.Pro509Leufs*39) in the LMNA gene and results in an mutant lamin A protein product. The main symptoms of the pathogenic variant carriers were palpitation, fatigue, and syncope, which typically occurred around 20-years-old. AV-conduction block and non-sustained ventricular tachycardia were the first signs of disease and would rapidly progress to atrial standstill around 30-years-old. Significant right atrial enlargement and bicuspid aortic valve malformation was also commonly seen in patients who carried this pathogenic variant.The pathogenic variant of c.1526del p.P509Lfs*39 was a frameshift deletion located at exon 9 of LMNA chr1:156137145 and causes severe right atrial enlargement, sick sinus syndrome, atrial standstill, ventricular tachycardia, and bicuspid aortic valve malformation. Our findings expand the phenotypic spectrum of novel LMNA gene mutations.